PENYUSUNAN ALLOMETRIK UNTUK PENDUGAAN KANDUNGAN BIOMASSA JENIS BAKAU (Rhizophora apiculata) - Didi Ali Hamidi; Wahyuni Ilham; Siti Aminah; Abdi Fithria (Universitas Lambung Mangkurat, 2014)
Mangrove forests have ecological functions as an absorber of carbon dioxide and store carbon through photosynthesis. How much carbon stored in mangrove forest can be estimated by biomass contained as an individual constituent mangrove forest vegetation. This research aims to develop allometric model to estimate content of biomass on Rhizophora apiculata which is one of the compilers specific of the mangrove forest. Research methods through logging (destruction) with a total sample of 35 trees that represents the distribution diameter of 11-78 cm. The results showed content of the biomass species Rhizophora apiculata as much as 77% on the trunk, 14% on the branch, 6% on the twigs and 3% on the leaves. Allometric are obtained to estimate the biomass content on Rhizophora apiculata types are as follows: Y = 0,1488D2,4310; branch section Y = 0.0229D2,4521; twigs part Y = 0.0375D2,0389; leaf Y = 0.1898D1,2809; total tree Y = 0.2300D2,3766. Through determination test concluded that the allometric chosen is Y = 0.2300D2,3766 with the value of the determinant coefficient of 0.9479